The Dictyostelium Model for Mucolipidosis Type IV - Allan, Claire Y.; Fisher, Paul R. (Frontiers in Cell and Developmental Biology, 2022)
Mucolipidosis type IV, a devastating neurological lysosomal disease linked to mutations in the transient receptor potential channel mucolipin 1, TRPML1, a calcium permeable channel in the membranes of vesicles in endolysosomal system. TRPML1 function is still being elucidated and a better understanding of the molecular pathogenesis of Mucolipidosis type IV, may facilitate development of potential treatments. We have created a model to study mucolipin function in the eukaryotic slime mould Dictyostelium discoideum by altering expression of its single mucolipin homologue, mcln. We show that in Dictyostelium mucolipin overexpression contributes significantly to global chemotactic calcium responses in vegetative and differentiated cells. Knockdown of mucolipin also enhances calcium responses in vegetative cells but does not affect responses in 6–7 h developed cells, suggesting that in developed cells mucolipin may help regulate local calcium signals rather than global calcium waves. We found that both knocking down and overexpressing mucolipin often, but not always, presented the same phenotypes. Altering mucolipin expression levels caused an accumulation or increased acidification of Lysosensor Blue stained vesicles in vegetative cells. Nutrient uptake by phagocytosis and macropinocytosis were increased but growth rates were not, suggesting defects in catabolism. Both increasing and decreasing mucolipin expression caused the formation of smaller slugs and larger numbers of fruiting bodies during multicellular development, suggesting that mucolipin is involved in initiation of aggregation centers. The fruiting bodies that formed from these smaller aggregates had proportionately larger basal discs and thickened stalks, consistent with a regulatory role for mucolipin-dependent Ca2+ signalling in the autophagic cell death pathways involved in stalk and basal disk differentiation in Dictyostelium. Thus, we have provided evidence that mucolipin contributes to chemotactic calcium signalling and that Dictyostelium is a useful model to study the molecular mechanisms involved in the cytopathogenesis of Mucolipidosis type IV.